Modelling of ionosphere behaviour prior to large earthquakes - Rizal, Nur Awatiff Mohamad (Universiti Sains Malaysia, 2017)
This project examines the behavior of pre-earthquake ionospheric parameters by the variation in foF2 (critical frequency of F2 layer) and TEC (total electron content) from the ionosondes stations. The data from a week before and after the main shock of an earthquake is analyzed to observe and model the behavior of the foF2 and TEC before the earthquakes (EQs). Monitoring these parameters is one of the methods of recent study to aim in reducing the damage of the natural hazards. Normally, a precursor alone is not enough to give an accurate and precise prediction of the earthquake. Therefore, it is important to exploit more on this study. Besides, the region of the study (Sumatra region) is a region that where the earthquake happened quite frequent. So, this study basically, to help and study whether the Sumatra’s earthquake gave the same anomalies like other studies. This study involving all of the Sumatra’s earthquake with a large magnitude (M> 6) in a range of 20 years from the year 1996 until 2016. The behavior of the chosen parameters will be discussed in the next chapter based on the listed earthquake within the year, and region of the study.